(3QSGdI Edi CHj LYaQ Hf eMeO Hf GdMSf Hf eMeO GdeQRHGfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3cJGHi CWGd Gddg HbGA GdaGVd GdChMO BOGe Gddg YRg hcd CUGH ef hLg hCNWC ef hLg Efg EfeG jNhV ai HjGf fbGA GdfaS Ch YOegG YfO GdehJ s
(3BNQgG (B:s
(3hdYd Gddg jSgd eYg GdEdJbGA ajchf ESJaGOI hEaGOI hdjYPQfi ai JThjT GdNW hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdhGMO hYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs